Effect of Replacing Rice Polish with Mulberry (Morus alba) Leaf Powder in Diet Containing Phytase Enzyme on Performance and Haemato-biochemical Parameters of Commercial Laying Hens - Siddiqui, Rukkiya; Mondal, Bidhan C.; Kumar, Ripusudan; Kaur, Manveen; Kumar, Ashoka; Palod, Jyoti; Lata, Manju (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The study was carried out to discern the effect of replacing rice polish with mulberry (Morus alba) leaf powder in a diet containing  phytase enzyme on growth performance, nutrient utilization, egg quality, and haemato-biochemical parameters of commercial laying  hens. Seventy-two 28-week-old White Leghorn laying hens were subjected to 12 weeks feeding experiment. Hens were randomly  distributed into four treatment groups with 18 birds per treatment. Hens of T1 (control) group were fed with basal diet, whereas in T2,  T3, and T4 groups, rice polish was replaced with mulberry leaf powder at 1/3rd, 2/3rd, and complete levels, respectively. A fixed level of  phytase enzyme at 250 FTU was included in all four treatment groups. The results indicated that the overall cumulative performance  of the laying hens in terms of feed intake, egg production, and FCR was not affected significantly. Dry matter utilization and yolk color  were significantly (p
Keywords: Mulberry leaf powder; Nutrient utilization; Phytase; Pigmentation